The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.639660
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Association Studies for the Detection of Genetic Variants Associated With Daptomycin and Ceftaroline Resistance in Staphylococcus aureus

Abstract: BackgroundAs next generation sequencing (NGS) technologies have experienced a rapid development over the last decade, the investigation of the bacterial genetic architecture reveals a high potential to dissect causal loci of antibiotic resistance phenotypes. Although genome-wide association studies (GWAS) have been successfully applied for investigating the basis of resistance traits, complex resistance phenotypes have been omitted so far. For S. aureus this especially refers to antibiotics of last resort like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…However, in a previous study applying GWAS to a collection of DAP-resistant S. aureus , no association to mutational changes in gdp P was observed [57]. Furthermore, in the strain collection described here, none of the MRLM isolates examined were DAP resistant.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, in a previous study applying GWAS to a collection of DAP-resistant S. aureus , no association to mutational changes in gdp P was observed [57]. Furthermore, in the strain collection described here, none of the MRLM isolates examined were DAP resistant.…”
Section: Resultsmentioning
confidence: 56%
“…In addition to β-lactam resistance in S. aureus , gdp P mutations have also been implicated in DAP non-susceptibility in enterococci. However, in a previous study applying GWAS to a collection of DAP-resistant S. aureus , no association to mutational changes in gdp P was observed [ 57 ]. Furthermore, in the strain collection described here, none of the MRLM isolates examined were DAP resistant.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have reported genome-wide association studies (GWAS) in cohorts of Mtb clinical isolates [16][17][18][19] and other bacterial pathogens [20][21][22] from around the globe. Many of the Mtb studies have identified drug resistance associated mutations in Rv2752c, here called rnj, encoding the ribonuclease RNase J.…”
Section: Introductionmentioning
confidence: 99%
“…Studying large isolate panels has been used to predict novel mechanisms of resistance. An analysis of 95 Staphylococcus aureus isolates was used to identify genes involved in daptomycin resistance, which was previously not well understood 185 , and a genome-wide association study suggested that convergent evolution has selected for daptomycin-resistant mprF mutants on multiple occasions 231 .…”
Section: Genomics and The Study Of Antimicrobial Resistancementioning
confidence: 99%